2008
DOI: 10.1590/s0100-879x2008005000015
|View full text |Cite
|
Sign up to set email alerts
|

Chlorpheniramine facilitates inhibitory avoidance in teleosts submitted to telencephalic ablation

Abstract: The present study investigated the involvement of H(1) histaminegic receptor on the acquisition of inhibitory avoidance in Carassius auratus submitted to telencephalic ablation. The fish were submitted to telencephalic ablation 5 days before the experiment. The inhibitory avoidance procedure included 1 day for habituation, 3 days for training composed of 3 trials each (1st day: T1, T2, T3; 2nd day: 2T1, 2T2, 2T3; 3rd day: 3T1, 3T2, 3T3) and 1 day for test. On training days, the fish were placed in a white comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
4
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 19 publications
(22 reference statements)
1
4
0
1
Order By: Relevance
“…Similar findings have been reported in several other studies (10,11,17,18). Thus, we believe that the results for the fish in the A-SAL and S-SAL groups were opposite in terms of memory consolidation of the inhibitory avoidance task due to the absence of cerebellar modulation in limbic structures in the ablation group, especially in the MP, which is thought to be homologous to the amygdala (29)(30)(31).…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Similar findings have been reported in several other studies (10,11,17,18). Thus, we believe that the results for the fish in the A-SAL and S-SAL groups were opposite in terms of memory consolidation of the inhibitory avoidance task due to the absence of cerebellar modulation in limbic structures in the ablation group, especially in the MP, which is thought to be homologous to the amygdala (29)(30)(31).…”
Section: Discussionsupporting
confidence: 89%
“…In this procedure, learning is inferred when the animal reduces its preference for dark places, which is an innate behavior of the species (16), associating the black compartment with an aversive experience. Several studies have used this model to investigate the action of different drugs on learning and memory processes and on processes of functional recovery in goldfish, indicating that the model is appropriate for this purpose (11,17,18).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The action of histamine (HA) is mediated by at least four types of receptors denoted H 1 , H 2 , H 3 , and H 4 (2). Studies have indicated the importance of the neural histaminergic system (NHS) in animal behaviors, primarily anxiety (3), learning and memory (4,5). Recent reports have also provided some insight about the involvement of the NHS in Alzheimer's disease (6,7) and state-dependent memory (8).…”
Section: Introductionmentioning
confidence: 99%
“…Em estudos com peixes, um modelo de ansiedade que vem sendo utilizado é o modelo de esquiva inibitória (Faganello & Mattioli, 2008;Garção & Mattioli, 2009). Esse modelo é baseado na preferência por ambientes escuros e aversão a ambientes claros que diversas espécies de peixes teleósteos apresentam (Gouveia Jr. et al, 2007).…”
unclassified